Answer:
The value at x =3 is undefined for the given expression
Step-by-step explanation:
Given expression is [tex]\frac{2x^2+8x}{(x+4)(x^2-9)}[/tex]
To find for what value of x is undefined in the given expression :
[tex]\frac{2x^2+8x}{(x+4)(x^2-9)}=\frac{2x(x+4)}{(x+4)(x^2-9)}[/tex]
[tex]=\frac{2x}{x^2-9}[/tex]
[tex]\frac{2x^2+8x}{(x+4)(x^2-9)}=\frac{2x}{x^2-9}[/tex]
If we put x=3 in the above expression we get
[tex]\frac{2x}{x^2-9)}=\frac{2(3)}{3^2-9}[/tex]
[tex]=\frac{6}{9-9}[/tex]
[tex]=\frac{6}{0}[/tex]
Therefore [tex]\frac{2x^2+8x}{(x+4)(x^2-9)}=\frac{6}{0}[/tex]
The value at x =3 is undefined for the given expression